The Integration of Legal Education and Mental Health Education of College Students in the Contemporary Network Environment Facing the Cultivation of Civic Awareness. (30th July 2022) - Li, Yong; Bao, Chuang; Liu, Ming
Abstract : Since the world entered the era of network information, the influence of the Internet has been expanding day by day, and today's college students are deeply affected by the network environment, which has also brought unprecedented challenges to the moral education work of colleges and universities. The rule of law education for college students is a key point for the comprehensive implementation of the strategy of governing the country by law. How to enhance the effectiveness and recognition of the rule of law education for college students has become an important task of higher education. Therefore, strengthening the legal education of college students is not only an inevitable choice to fully implement the rule of law but also a realistic requirement to improve the level of higher education and realize the all-round development of college students. College students' mental health education is an important part of the talent training system of colleges and universities, and in-depth exploration of the ideological and political laws of college students' mental health education courses is an inevitable requirement for implementing the fundamental task of Lide Shuren. College students' mental health education courses must be integrated into the ideological and political concepts of the curriculum, reflect the political orientation of ideological and political work, embody the law of educating people with morality as the first, and embody the practical purpose of psychology to pay attention to personality improvement. It is necessary to optimize the content of education and teaching, excavate the elements of ideological politics in the curriculum, enrich the resources of ideological politics in the curriculum, and explore a new way of reforming the ideological and political education curriculum for college students from the aspects of deeply planting family and national feelings, enhancing political identity, strengthening cultural self-confidence, cultivating Chinese temperament, clarifying the meaning of life, strengthening mission responsibility, enhancing civic awareness, and developing law-abiding habits. Strictly regulate the behavior of contemporary college students in the online environment, give full play to the role of legal education, and reduce the incidence of online incidents such as online fraud and cyber violence. This paper puts forward some problems in the current legal education of college students in China and points out the root causes of these problems. Methods for structural reform and advanced cultural construction based on social development are proposed. From a strategic point of view, it is believed that only by managing the reform of legal education and cultivating civic awareness can we completely solve various contradictions and problems among college students in the network environment and pave the way for the development of college students.